Vivências ludopoiéticas no jogo de areia: a tatilidade na autoformação humanescente - Oliveira, Narla Sathler Musse de (2011)
This study presents the ludopoietic experiences in Sandplay and the expression of tactility in humanescente self-training of future teachers of geography. The overall objective was to analyze and interpret as the tactility in the ludopoietic experiences with Sandplay facilitates the sentipensar and boosts the humanescent self-training. The qualitative research approach follows the principles of existential research-action into the etnofenomenologic perspective, that considers studies of the ethnography and the phenomenology with ethnomethodology. In this study we used the sedimentary rock called sandstone and your mineral grains as cognitive operator to stimulate the discussions of the ludopoietic experiences in Sandplay. The members of research were students of the Geography degree of IFRN. To achieve the research objectives were organized experiential meetings and virtual meetings. The ludopoietic experiences in Sandplay revealed the impact of tactility to humanescente self-training, indicating the importance of touch for apprehend and experience the world with beauty, joy and tenderness. These experiences showed the ludopoietic system properties, the threads of embodiment and the meaning of the sentipensar of tactility as a phenomenon that drives the humanescent self-training, evidenced by etnofenomenologie. Data were obtained through Sandplay, sensitive listening, experiential diary, photographic and movie records. In the process of data analysis were revealed the of etnofenomenological principles of experientiality indiciality, reflexivity, self-organizability, filiability, archetypality and humanescencialidade. Through the tactility, the Sandplay favors the awareness of the condition of being, takes life stories, providing the construction of knowledge in a meaningful and contextual way